Partner HIV Serostatus Impacts Viral Load, Genital HIV Shedding, and Immune Activation in HIV-Infected Individuals. (1st September 2019) - Jaumdally, Shameem Z.; Liebenberg, Lenine J.P.; Gumbi, Pam P.; Little, Francesca; Jaspan, Heather B.; Gamieldien, Hoyam; Tiemessen, Caroline T.; Coetzee, David; Martin, Darren P.; Williamson, Carolyn; Williamson, Anna-Lise; Passmore, Jo-Ann S.
Abstract : Abstract: Studies of seronegative individuals in HIV discordant relationships provide important insights into the effects of HIV exposure on the seronegative partner, but few have examined the impact of partner serostatus on disease progression in seropositive individuals. We investigated the impact of HIV serostatus on clinical and biological factors influencing HIV disease progression in 337 HIV-infected heterosexual individuals in stable long-term HIV-seroconcordant or HIV-serodiscordant relationships. Seroconcordant individuals had significantly higher plasma viral loads (pVLs) than HIV-infected partners in serodiscordant partnerships [4.4 log10 copies RNA/mL (interquartile range 3.7–5.0) versus 3.9 (3.3–4.5), P < 0.0001], irrespective of gender. pVLs correlated inversely with CD4 + T-cell counts, although CD4 counts did not differ significantly between seroconcordant and serodiscordant individuals. HIV+ seroconcordant individuals had higher frequencies of CCR5 + CD4 and CD8 T cells ( P = 0.03 and P = 0.02, respectively) than HIV+ individuals in serodiscordant relationships and higher concentrations of plasma IL-1β ( P = 0.04), TNF-α ( P = 0.02), and IL-10 ( P = 0.02). Activated CD4 + T-cell frequencies and TNF-α were the most influential in determining variation in pVLs, independently of CD4 counts. In addition, HIV+ seroconcordant women had significantly higher genital VLs (gVLs) than HIV+ women in serodiscordant relationships ( P < 0.001), with pVLs correlating significantly with gVLs (Rho = 0.65, P < 0.0001). Cervical and blood T-cell activation tended to correlate positively, although partner seroconcordance did not influence genital T-cell activation. We conclude that HIV+ seroconcordant individuals have higher frequencies of activated, CCR5-expressing T cells in blood and higher pVLs and gVLs than their HIV+ counterparts in discordant relationships, which could translate to faster disease progression or larger viral reservoir. Abstract : Supplemental Digital Content is Available in the Text.